(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the role of the lexicon in foreign language teaching, the formation and development of foreign language teaching skills, as well as the communicative method in teaching the lexicon, and the difficulties in teaching the lexicon of a foreign language.